PERANG OBOR Upacara Tradisi di Tegal Sambi, Tahunan, Jepara - Aristanto, Zaenal (Sabda: Jurnal Kajian Kebudayaan, 2011)
Torch war is a traditional attraction that must be preserved as a local grateful expression to God on post-harvest favor. This article discusses a ceremony procession with symbolic meaning as practiced in Tegal Sambi village, Tahunan, Jepara, where communities believe that this ceremony of torch war can avoid misfortune and calamities to the village and villagers.